FREQUENT COLLOCATION OF ADJECTIVE-NOUN AND NOUN-ADJECTIVE: CORPUS ANALYSIS - Fransiska Selvy Wulandari; Barli Bram (JURNAL ILMIAH BAHASA DAN SASTRA, 2019)
This paper investigated frequent collocations used by English learners. Specifically, it is a corpus-based study which focuses on the frequencies of 15 pairs of adjective-noun and noun-adjective collocations. The frequency was examined in two corpora, namely the Corpus of Contemporary American English (COCA) and the British National Corpus managed by Brigham Young University (BYU-BNC). The collocations are presented in the form of pairs to give the comparisons of frequencies between frequently used collocations and less frequently used ones, as seen in the corpora although they have a similar meaning. The present study aims to help English learners to be familiar with the more appropriate word choice used in their writing and speaking.